KADAR AIR, TOTAL VOLATIL NITROGEN (TVN) SERTA SIFAT SENSORIS IKAN BANDENG ASAP CAIR KEMASAN VAKUM BEDASARKAN VARIASI SUHU DAN LAMA PENYIMPANAN - Yusuf Hamdani; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2020)
Storage of milkfish liquid smoke vacuum packaging is stored with variations in temperature (room temperature and cold temperature) and storage time. The aim of this study was to determine the effect of milkfish storage in vacuum packaging liquid with temperature variations (room temperature and cold temperature) as well as storage time on moisture content, TVN and sensory properties. This study used a Completely Randomized Design (CRD) consisting of 2 factors, factor I was variation in temperature (room temperature and cold temperature) and factor 2 was storage time (0, 5, 10, 15 and 20 days). The results of the research on TVN levels and moisture content showed that all treatments both time and temperature variations during storage were 20 days, the levels of TVN and moisture content still met SNI. Sensory testing of the color of the texture and aroma of all treatments both time and temperature variations are not significantly different. except for the texture stored in cold temperatures on the 10th and 20th days, it is significantly different